Multisystem Langerhans Cell Histiocytosis following Treatment of Initially Presumed Atopic Dermatitis with Dupilumab: A Case Report of an Extremely Confusing Scenario - Wenhao Cheng; Hong Ren; Wenlong Hu (Karger Publishers, 2024)
Introduction: Atopic dermatitis (AD) is a common chronic, recurrent, and non-infectious inflammatory skin disease. Dupilumab is a human monoclonal antibody with clinical efficacy in severe AD and has a good safety profile. Case Presentation: We hereby describe a previously unreported case of multisystem Langerhans cell histiocytosis (MS-LCH) that is associated with a history of AD treatment using dupilumab. Conclusion: A single case of MS-LCH with a history of dupilumab treatment for AD was described for the first time. This case highlights that given its susceptibility to skin involvement, LCH needs to be considered as a differential diagnosis for skin lesions that are not improved by established therapies.